Cross‐nucleation of polybutene‐1 Form II on Form I seeds with different morphology. Issue 2 (5th February 2020) - Wang, Wei; Wang, Bao; Carmeli, Enrico; Wang, Zefan; Ma, Zhe; Cavallo, Dario
Abstract: Polybutene‐1 (PB‐1) trigonal Form I crystals with different morphologies, namely spherulitic, hedritic, and fibrous, were used as seeds to quantitatively study the cross‐nucleation kinetics of the tetragonal Form II. Interestingly, a large difference in the cross‐nucleation ability of the various Form I seeds was observed. The Form I fiber exhibits the fastest cross‐nucleation, followed by the hedrite and eventually by the spherulite. The nucleation induction time was quantified from the evolution of the transmitted light intensity via polarized optical microscopy. The data were tested against different nucleation models, revealing that the rate‐determining step for nucleation is the growth of the nucleus to attain the critical dimension, rather than the formation of the first crystalline layer in contact with the substrate. In addition, for spherulitic seeds, a meaningful dependence of cross‐nucleation induction time on Form I lamellar thickness was found, with the kinetics being faster for higher original seed's crystallization temperatures. The results were interpreted assuming a free energy barrier for cross‐nucleation which is a function of the mismatch between the daughter and the parent polymorphs' lamellar dimensions. This aspect, together with the calculated low values of interfacial free energy difference parameter for nucleation, suggests the possible existence of an epitaxial relationships between cross‐nucleating PB‐1 Form II and Form I. Abstract : Crystals of polybutene‐1 Form II are able to nucleate on pre‐existing seeds of Form I. We measured the nucleation induction time on Form I trigonal seeds possessing various morphologies. Form I fibers display the highest nucleating efficiency, followed by hedrites and eventually spherulites. Differences in the free energy barrier for cross‐nucleation, as a result of size mismatch between the parent and daughter polymorphs' crystallites, are proposed to be the origin of the observed trend.